CFD MODELING OF SYNGAS DISPERSION AND CONSEQUENCE FOR BIOMASS PROCESS INDUSTRY - ZAINA ABIDIN, NOOR AZURAH (2014)
Enthusiasm to acquire advanced technology for renewable energy generation has drowned the noteworthy of safety especially related to biomass plant. Many instances describe the use of biomass could reduce the impact of greenhouse gases. Although these materials may have become fuel for the future, but with regards to safety issues, it is still uncertain. Utilization of biomass as a source of gasification makes it differ from other energy conversion technologies since it intrinsically involves mostly toxic and flammable gas mixtures along the process. Any loss of containment, particularly concerning leakage and rupture of pipelines and vessels may lead to serious accidents. Hence, fundamental studies with regards to the safety issues are indispensable. Lacking of information pertaining to this matter makes it difficult to predict the dispersion of flammable and toxic gas mixtures from this plant, let alone the consequences.